Identification of Differentially Methylated Regions (DMRs) between Embryonic Stem Cells (ESCs) and Embryonic Germ Cells (ESCs) by DNA methylation studies - Lynn, Khoo Jo (2018)
Epigenetic is the study of heritable changes that are not caused by the changes in the DNA sequence. It involves post–translational modifications of histones and cytosine modifications, resulting in long–term alterations in the transcriptional potential of a cell that are not necessarily heritable. One of the major epigenetic events, known as genomic imprinting, is a phenomenon in which some genes are expressed in a parent–of–origin–specific manner. To date, over 100 genes are known to be regulated by genomic imprints, many of which have significant roles for embryogenesis, placental formation and brain development. In this study, embryonic stem cells (ESCs) and embryonic germ cells (EGCs) were used. ESCs are pluripotent stem cells derived from inner cell mass (ICM) of pre–implantation embryos called blastocyst, while EGCs are pluripotent stem cells originated from primordial germ cells (PGCs). Although genomes of ICM cells are globally hypomethylated, primary DNA methylation imprints are retained in ICM and its derivatives, i.e. ESCs. Therefore, monoallelic imprinted gene expression will be established in ESCs upon differentiation. In contrast, PGCs colonised in the gonads have undergone global DNA demethylation, by which DNA methylation imprints are supposed to be erased. Thus, ESCs and EGCs are highly similar cells except for one aspect, that is, the imprinting status. Comparison of ESCs with EGCs may uncover epigenetic modifications required for the establishment of imprinted gene expression. Toward this end, ESCs and EGCs were differentiated by embryoid body formation and harvested every other day, being verified by qPCR and allele specific expression. Methylation of imprints were confirmed to be retained in ESCs but not EGCs at both undifferentiated and differentiated state by Reduced Representative Bisulfite Sequencing (RRBS) and SureSelectXT Methyl–Seq Combined with Post–Bisulfite Adaptor Tagging (SureSelect–PBAT) methods. A number of differentially methylated regions (DMRs) other than known imprinted regions were identified for the first time between ESCs and EGCs. Interestingly, DMRs that are hypermethylated in EGCs while being hypomethylated in ESCs were also able to be identified. Although some of these DMRs were technically validated, methylation levels showed were different from that of RRBS and SureSelect–PBAT method. Nonetheless, these DMRs still exhibited the same hypermethylated/hypomethylated state in ESCs/EGCs. Gene expression studies by RNA–seq demonstrated that only a small proportion of genes with 2–or more–fold difference in expression between ESCs and EGCs were able to be correlated with their methylation levels, as most of the DMRs were identified at intron and intergenic regions, not promoter regions.